Bacillus licheniformis escapes from Myxococcus xanthus predation by deactivating myxovirescin A through enzymatic glucosylation - Chuandong Wang; Xinlin Liu; Peng Zhang; Yan Wang; Zhifeng Li; Xun Li; Renqing Wang; Zhaohui Shang; Jingen Yan; Haifeng He; Jing Wang; Wei Hu; et al. (Environmental Microbiology, 2019)
Summary Myxococcus xanthus kills susceptible bacteria using myxovirescin A (TA) during predation. However, whether prey cells in nature can escape M. xanthus by developing resistance to TA is unknown. We observed that many field‐isolated Bacillus licheniformis strains could survive encounters with M. xanthus , which was correlated to their TA resistance. A TA glycoside was identified in the broth of predation‐resistant B. licheniformis J32 co‐cultured with M. xanthus , and a glycosyltransferase gene ( yjiC ) was up‐regulated in J32 after the addition of TA. Hetero‐expressed YjiC‐modified TA to a TA glucoside (TA‐Gluc) by conjugating a glucose moiety to the C‐21 hydroxyl group, and the resulting compound was identical to the TA glycoside present in the co‐culture broth. TA‐Gluc exhibited diminished bactericidal activity due to its weaker binding with LspA, as suggested by in silico docking data. Heterologous expression of the yjiC gene conferred both TA and M. xanthus ‐predation resistance to the host Escherichia coli cells. Furthermore, under predatory pressure, B. licheniformis Y071 rapidly developed predation resistance by acquiring TA resistance through the overexpression of yjiC and lspA genes. These results suggest that M. xanthus predation resistance in B. licheniformis is due to the TA deactivation by glucosylation, which is induced in a predator‐mediated manner.